A simulation-based approach to business model design and organizational Change. Issue 1 (2nd January 2021) - Bock, Adam J.; Warglien, Massimo; George, Gerard
ABSTRACT: While several practice-based approaches of business model design suggest ways to create new business models, there is limited understanding of why and how business models change. This exploratory study employs neural network analysis to simulate business model design and business model change. We conceptualise business model design as a schema of the organisation's critical resources, transactions, and value proposition. Elements of the schema are connected in a simple neural network. The network evolves based on a constraint satisfaction network until it converges to a stable state of a coherent business model. An in-depth case study of an entrepreneurial venture provides a real-world example to test the analytical framework. Using data from the case study, we run multiple simulations of business model design and business model change. The results suggest that business model change can be understood as a form of constraint satisfaction, linking managerial cognition with business model change. The simulation approach also helps identify possible, but unrealized business models. This novel approach paves the way for new research and practice in business model design and change.